Transformative Leadership and Innovative Behavior in Medical Education: Mediating Effects of Psychological Empowerment and Creative Self-Efficacy - Wilaphan, Kotchaphan; Noawanit, Songkram; Ngudgratoke , Sungworn (The Journal of Behavioral Science, 2023)
Developing innovative behavior among employees is one of the approaches supported to enhance quality human resources to function well in the organization and gain an advantage over competitors. The aims of the study were to investigate the relationship between transformational leadership and innovative behavior, with psychological empowerment and creative self-efficacy as mediating variables. Data were collected from 153 staff members of a medical school in Thailand via self-reported questionnaires. The results of structural equation modeling (SEM) indicated that transformative leadership was significantly and positively associated with all variables studied: innovative behavior (β = .49; t = 11.92; p < .001), psychological empowerment (β = .84; t = 15.72; p < .001), and creative self-efficacy (β = .83; t = 12.47; p < .001). It was also found that, psychological empowerment (β = .21; t = 2.40; p = .05) and creative self-efficacy (β = .54; t = 10.00; p < .001) were positively and significantly associated with innovative behavior. In addition, only creative self-efficacy partially mediates the relationship between transformative leadership and innovative behavior (β = .49; p < .001), while psychological empowerment does not (β = -.13; p > .05). The study recommends that medical school managers enhance transformative leadership through creative self-efficacy to foster higher innovative behavior among staff.